2012
DOI: 10.1038/bmt.2012.187
|View full text |Cite
|
Sign up to set email alerts
|

Risk and prognostic factors for acute GVHD based on NIH consensus criteria

Abstract: To investigate the risk factors for acute GVHD (aGVHD), based on NIH consensus criteria (NCC), we evaluated 775 patients who underwent allogeneic transplantation. Of them, 346 patients developed aGVHD by NCC, in whom we also analyzed factors affecting aGVHD-specific survival. The cumulative incidence of aGVHD was 44.7%, consisting of classic aGVHD (n ¼ 320) and late-onset (n ¼ 26). Multivariate analyses revealed that younger age (P ¼ 0.015), unrelated donors (P ¼ 0.004) and acute leukemia compared with other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 20 publications
3
55
1
1
Order By: Relevance
“…Wide variation exists in prior estimates of incidence of LA GVHD. [2][3][4][18][19][20][21] Our data support an incidence of 11% at 2 years after HCT. De novo onset LA GVHD is more common in patients undergoing reduced intensity HCT.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Wide variation exists in prior estimates of incidence of LA GVHD. [2][3][4][18][19][20][21] Our data support an incidence of 11% at 2 years after HCT. De novo onset LA GVHD is more common in patients undergoing reduced intensity HCT.…”
Section: Discussionsupporting
confidence: 73%
“…Although reclassification following the NIH Consensus Conference improved diagnostic criteria, 1 subsequent retrospective analyses have not uniformly found that LA GVHD has a prognosis distinct from acute or chronic GVHD. [2][3][4][5][6][7] Improved understanding of LA GVHD is needed prior to development of There is an Inside Blood Commentary on this article in this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Anesseti et al showed that the incidence of aGVHD with the use of pBsc was about the same as in bone marrow (BM) however the incidence of cGVHD was increased by 16% as compared to bone marrow (26). The use of double unit umbilical cord transplant (dUcB) has been associated with lower incidence of cGVHD but higher incidence of aGVHD (27). other studies have reported no impact of stem cell source on aGVHD (28)(29)(30).…”
Section: Risk Factorsmentioning
confidence: 99%
“…aGvHD and cGvHD were scored according to the NIH Consensus Conference and the Glucksberg criteria 23 as described previously in detail. [24][25][26] aGvHD was graded by staging the affected organs, particularly skin, liver and gut (stage 1-4) and subsequently determining an overall grade (grade I-IV). 2 Grading of cGvHD was performed by scoring the organ involvement (score 0-3) and global severity grading (mild, moderate, severe).…”
Section: Patients and Ecp Treatmentmentioning
confidence: 99%